2015
DOI: 10.2147/copd.s74641
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in COPD: an unmet area for quality improvement

Abstract: COPD is a leading cause of morbidity and mortality worldwide. Patients suffer from refractory breathlessness, unrecognized anxiety and depression, and decreased quality of life. Palliative care improves symptom management, patient reported health-related quality of life, cost savings, and mortality though the majority of patients with COPD die without access to palliative care. There are many barriers to providing palliative care to patients with COPD including the difficulty in prognosticating a patient’s cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(98 citation statements)
references
References 70 publications
0
94
0
4
Order By: Relevance
“…Our results are corroborated by Curtis et al, who conclude that palliative care services are an important opportunity for improving end-of-life care. 31 Although certain health systems may currently not be designed to adequately reimburse palliative care treatments, 32 other possible explanations for low use of available palliative care in COPD patients may include different factors such as provider failure to recognize the imminent death of patients with COPD, the perception that palliative care services are available only to cancer patients, the assumption that the provided care is sufficient, or the belief that a terminal COPD patient already received palliative care elsewhere, such as in a long-term care facility. 7,18 Given that the use of a specific intervention is affected by disease stage, the individual's functional status, and the best evidence available at that time, not every intervention can be labeled as futile care.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are corroborated by Curtis et al, who conclude that palliative care services are an important opportunity for improving end-of-life care. 31 Although certain health systems may currently not be designed to adequately reimburse palliative care treatments, 32 other possible explanations for low use of available palliative care in COPD patients may include different factors such as provider failure to recognize the imminent death of patients with COPD, the perception that palliative care services are available only to cancer patients, the assumption that the provided care is sufficient, or the belief that a terminal COPD patient already received palliative care elsewhere, such as in a long-term care facility. 7,18 Given that the use of a specific intervention is affected by disease stage, the individual's functional status, and the best evidence available at that time, not every intervention can be labeled as futile care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our preliminary results indicate a TPCC model may help to stabilize or improve multiple symptoms. Several studies have identified the high symptom burden of end‐stage heart and lung disease, yet palliative care integration into noncancer disease management remains poor and inconsistent …”
Section: Discussionmentioning
confidence: 99%
“…That concern is amplified by the recognition that early palliative care involvement and expertise benefits not only cancer patients, but also patients with life-limiting nonmalignant disease such as congestive heart failure and chronic obstructive pulmonary disease 16,17 .…”
Section: What Are the Barriers To Implementation?mentioning
confidence: 99%